Polish Privacy Media Discourse: Privacy as Imposed Policies - Wojtkowski, Łukasz (2020)
In this article we look at the Polish media discourse on privacy. In the analysis, we draw on theoretical approaches that understand privacy as having four dimensions: Relational, participatory, contextual, and technological. Moreover, we seek whether a specific norm of data-related privacy could be defined/redefined within the discourse. Considering the post-communist past that shapes a specific approach to surveillance and the general polarisation of polish media discourse, one would expect the key role of privacy issues in the public sphere. Thus, applying a critical discourse studies analysis, the aim was to capture the character of the so far under-researched privacy in Polish media discourse. We study what types of institutional agents are mentioned as creating privacy policies and what dimensions of privacy they tackle. Moreover, we also try to capture whether the institutional position offers a specific normative understanding of privacy and whether this norm is citizen/user-oriented. The results of the study indicate that: both the media discourse and the normative content of privacy policies are dominated by legal aspects concerned with the issues resulting from EU regulations (i.e., General Data Protection Regulation); privacy policies are institutionally dispersed and monopolised by journalists and experts instead of state officials or politicians; and there is only limited evidence of a discursive frame of a citizen-oriented norm of how to protect data-related privacy.